2009
DOI: 10.1890/08-1569.1
|View full text |Cite
|
Sign up to set email alerts
|

Interpopulation divergence in competitive interactions of the mosquitoAedes albopictus

Abstract: Geographic variation in species interactions can have major effects on distributions. Effects of such variation can be particularly evident for invasive species, in which variation in competitive ability can influence invasive success and impacts. We tested the hypothesis that coexistence or exclusion of the resident mosquito Aedes aegypti results from variation among local populations of the invasive Aedes albopictus in competitive interactions with A. aegypti. We also examined the role of variation in fecund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 43 publications
(88 reference statements)
3
56
0
1
Order By: Relevance
“…Higher temperatures can increase immature development rate [85,86], although heat can also directly reduce persistence of aquatic container habitat [85]. Numerous studies have shown that numbers of water-filled containers and larval mosquitoes are both less abundant in dry conditions [73,87,88]. Thus, extreme heat may reduce adult mosquito production in urban areas where disused containers are the predominant habitat for immature development.…”
Section: Resultsmentioning
confidence: 99%
“…Higher temperatures can increase immature development rate [85,86], although heat can also directly reduce persistence of aquatic container habitat [85]. Numerous studies have shown that numbers of water-filled containers and larval mosquitoes are both less abundant in dry conditions [73,87,88]. Thus, extreme heat may reduce adult mosquito production in urban areas where disused containers are the predominant habitat for immature development.…”
Section: Resultsmentioning
confidence: 99%
“…Satyrization may suppress A. aegypti populations, whereas the development of resistance to satyrization may allow recovery. In combination with other biotic and abiotic factors (47,48), this interplay could account for the observed patchy distributions of these two species where they encounter one another (e.g., refs. 49 and 50).…”
Section: Discussionmentioning
confidence: 99%
“…japonicus and Ae. triseriatus is sustained under different environmental conditions (e.g., resource type, temperature, predation) and geographic populations (Leisnham et al 2009). In eastern United States, Ae.…”
Section: Discussionmentioning
confidence: 99%